The involvement of effector memory CD4+ T cells in mediating the impact of genus Oscillibacter gut microbiota on Alzheimer’s disease: a Mendelian randomization study - Zhang, Huachang; Wang, Yudong; Zhao, Hui; Wang, Wei; Han, Fabin (Frontiers in Aging Neuroscience, 2024)
Objective: This study aims to investigate the causal relationship between gut microbiota characteristics (207 taxa and 205 pathways) and Alzheimer's disease , and to determine and quantify the role of immune cells as potential mediators.Methods: Gut microbiota characteristics (207 taxa and 205 pathways) were obtained from the NHGRI-EBI GWAS Catalog project, while Alzheimer's disease data and 731 immune cell characteristics were obtained from the IEU Open GWAS project. Two-sample Mendelian randomization (MR) was conducted to determine whether gut microbiota characteristics (207 taxa and 205 pathways) were causally related to Alzheimer's disease. Furthermore, two-step MR was employed to quantify the proportion of the effect of immune cell characteristics mediated by gut microbiota characteristics (207 taxa and 205 pathways) on Alzheimer's disease.Results: 17 immune cell characteristics were identified as potential mediators for 13 gut microbiota influencing Alzheimer's disease, with Effector Memory CD4+ T cell Absolute Count accounted for 8.99% of the causal relationship between genus Oscillibacter and Alzheimer's disease.In summary, our research confirms a causal relationship between gut microbiota and Alzheimer's disease, with immune cells contributing to a significant portion of the effect. However, the full mediators of gut microbiota's impact on Alzheimer's disease remains unclear.Further investigation is warranted to explore additional potential risk factors acting as mediators.